Urgensi Kerjasama Intelejen dan Penindakan Kemigrasian serta Intelejen Keamanan Polri dalam Menghadapi Terorisme dan Tindak Pidana Perdagangan Orang - Pramula Mahrus Razzan; Radifan Syarofi Listikoaji; Zacki Ahta Sajjana (University of Merdeka Malang, 2026)
Terrorism and human trafficking in Indonesia have increasingly developed along with technological advancement, digitalization, and rising cross-border mobility. Both forms of crime are transnational, organized, and exploit gaps in inter-agency coordination, creating serious challenges for national security systems. This condition indicates that countermeasures cannot rely solely on repressive approaches, but also need to be strengthened through preventive, intelligence-based, and integrated strategies. This study aims to analyze the urgency of cooperation between the Directorate of Immigration Intelligence and Enforcement (Inteldakim) and the Police Security Intelligence Agency (Intelkam Polri) in addressing terrorism and human trafficking threats in Indonesia. The research employs a qualitative method with a normative juridical approach through library research of relevant literature, scientific journals, and legal regulations. The findings show that synergy between Inteldakim and Intelkam Polri plays an important role in strengthening early detection systems, improving the effectiveness of information sharing, and supporting faster and more accurate prevention efforts. This study also emphasizes the importance of establishing an integrated digital-based intelligence database system and real-time inter-agency data exchange mechanisms as concrete forms of strengthening national intelligence synergy. In addition, technical regulations governing operational coordination among institutions are needed to ensure a more integrated and effective response to security threats. Therefore, the integration of cooperation between both institutions becomes a strategic necessity in maintaining national security and stability amid evolving global threats.